2018
DOI: 10.31018/jans.v10i4.1922
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of early shoot borer, Chilo infuscatellus Snellen on sugarcane as influenced by weather conditions

Abstract: A field experiment on population dynamics of early shoot borer, Chilo infuscatellus Snellen on sugarcane was carried out during 2016-17 crop season at the research farm of CCS Haryana Agricultural University, Regional Research Station, Karnal. Studies on population dynamics revealed thathighest incidence (3.81 per cent in CoH 160, 4.60 per cent in CoH 119 and 3.12 per cent in CoS 767) of C. infuscatellus was recorded during 24th SMW. Correlation of C. infuscatellus population with various environmental factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 2 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…The data clearly show that the oviposition period took significantly longer than the pre-and post-oviposition periods. These findings are consistent with the finding of Kumar et al (2019), and Kalariya and Radadia (2014), who reported that pre, post and oviposition period varied from 0-1, 1-2 and 2-4 days, respectively, and the oviposition period was also longer than pre-and post-oviposition periods in their studies, fully supporting the current findings. The total life cycle, longevity, and sex ratio of a male and female were also recorded in this study.…”
Section: Infuscatellus Adult Stage Development (Days) In Lab Conditionssupporting
confidence: 93%
See 2 more Smart Citations
“…The data clearly show that the oviposition period took significantly longer than the pre-and post-oviposition periods. These findings are consistent with the finding of Kumar et al (2019), and Kalariya and Radadia (2014), who reported that pre, post and oviposition period varied from 0-1, 1-2 and 2-4 days, respectively, and the oviposition period was also longer than pre-and post-oviposition periods in their studies, fully supporting the current findings. The total life cycle, longevity, and sex ratio of a male and female were also recorded in this study.…”
Section: Infuscatellus Adult Stage Development (Days) In Lab Conditionssupporting
confidence: 93%
“…These findings are consistent with those of Kalariya et al (2014) who conducted the same experiment on C. infuscatellus in the laboratory and reported that the incubation period, larval and pupal duration were all recorded as short as possible, lending full support to the finding of the present study. Kumar et al (2019) conducted a study that is similar to this one but produced entirely different findings. They raised C. infuscatellus in a lab setting and found that the incubation time, larval timespan, and pupal period all took the maximum length of time.…”
Section: Infuscatellus Larval and Pupal Developmental Duration (Days)...mentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, it is evident from previous study of Abdullah et al (2006) that morphological characteristics of different sugarcane varieties showed association with the stem borer infestation. As such, a significant but negative correlation between stem borer infestation and total shoot length has been reported by Kumar et al (2018). Studies also reported that sheath length at bottom, mid and top cane portion also had association with the stem borer infestation and losses were decreased in canes with stronger bottom and mid portion sheath (Abdullah et al, 2005).…”
Section: Correlation Between Various Varietal Characters Of Sugarcane Varieties With Population and Infestation Of C Infuscatellus And Itmentioning
confidence: 85%
“…The life cycle duration of C. zacconius ranged between 40-65 days from our study which mirrors that of C. partellus and C. infuscatellus whose life cycles span between 34-66 days and 29-44 days respectively (Panchal and Kachole, 2013;Arunkumara et al, 2018;Peddakasim, et a.,. 2018;Kumar et al, 2019). The use of artificial diets for larval rearing have been reported to be successful and could also pose various challenges to many Lepidopteran larvae (Ngomane et al, 2022;Wei et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%